The value of contrast-enhanced ultrasound in differentiating benign from malignant retroperitoneal masses - Zadeh, Ehsan Safai; Görg, Christian; Prosch, Helmut; Görg, Mathis; Trenker, Corinna; Westhoff, Christina Carolin; Huber, Katharina Paulina; Pochepnia, Svitlana; Weber, Michael; Dietrich, Christoph Frank; Raab, Nils; Alhyari, Amjad; et al. (European journal of radiology, 2024)
Objectives - To evaluate the value of contrast-enhanced ultrasound (CEUS) perfusion patterns in the differentiation of benign and malignant retroperitoneal masses (RMs). - Methods - Between 2006 and 2023, 122 consecutive patients with an RM visualizable by B-mode US were investigated additionally with CEUS. On CEUS, the extent of enhancement (classified as marked, reduced, or absent) and the homogeneity of enhancement (HE; classified as homogeneous or inhomogeneous) were evaluated. Subsequently, the malignancy rate according to CEUS perfusion patterns was determined. - Results - On CEUS, marked enhancement was significantly more frequently associated with malignancy than with benignity (p < 0.0001, Fisher’s exact test). All lesions with no enhancement were benign. Regarding HE, there was no significant difference between benign and malignant lesions (p = 0.07, Fisher’s exact test). - Conclusion - On CEUS, marked enhancement in an RM may be indicative of a malignant lesion. Furthermore, absent enhancement can be considered to be an indication of benignity. The use of CEUS can be helpful in the evaluation of the malignancy of retroperitoneal masses.